PENINGKATAN MOTIVASI BERPRESTASI GURU MELALUI SUPERVISE AKADEMIK SD RAYON VI KECAMATAN TAMBANG KABUPATEN KAMPAR - Yusmarni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The purpose of this study was to determine whether teachers’ achievement motivation could be improved through academic supervision in elementary schools of Rayon VI, Mining District, Kampar Regency. The study was designed as action research conducted in two cycles, with each cycle consisting of planning, implementation, observation, reflection, and revision stages. The actions implemented included academic supervision, followed by commitment monitoring and professional guidance. Data were collected through observation, and the data were analyzed using descriptive statistical methods. Based on the analysis and discussion of the research data, it was concluded that academic supervision effectively improved teachers’ achievement motivation. The aspects of academic supervision conducted by supervisors showed an increase from the first to the second cycle. In the first cycle, the supervision aspect achieved a score of 28, while in the second cycle it improved significantly to a score of 43. Similarly, teachers’ achievement motivation increased from 60.1% in the first cycle, categorized as “fairly good,” to 81.6% in the second cycle, categorized as “very good.” These results indicate that academic supervision plays a significant role in enhancing teachers’ achievement motivation.